Women who surf : charging waves with the world's best - Marcus, Ben.; Griggi, Lucia (Unites States of America : Rowman & Littlefield, 2017)
Mavericks and more, a celebration of feminine beauty, athleticism, wisdom, and skill when the surf is bombing$1 (BWomen Who Surf profiles some of the world$1 (Bs most inspiring female surfers ranging from Bethany Hamilton to Wrenna Delgado. Each surfer tells her story, highlighting her personal challenges, accomplishments, and philosophy, as well as inspiring readers and providing them with practical how-to suggestions on maximizing not only their own potential in surfing but in life as they lead the charge and push their limits at infamous big-wave spots like Teahupoo in Tahiti, Waimea Bay, and Peahi/Jaws in the Hawaiian Islands.s
Rochelle Ballard - Kauai Pride -- Wrenna Delgado - Jersey shore to north shore -- Bethany Hamilton - Gotta have faith -- Maya Gabeira - She's so tough -- Keala Kennelly - Not fearless, bold -- Andrea Moller - Waterwoman -- Leah Dawson - Soul Salvation -- Mercedes Maidana - A concussionary tale -- Easkey Britton - Irish up -- Alana Blanchard - Born this way -- Bianca Valenti - Cold sweat -- Paige Alms - Maui Wowie! -- Alison Teal - The adventures -- Sally Fitzgibbons - The people's champion -- Rosy Hodge - The face, the voice -- Janet Macpherson - Surfisticate -- Pauline Ado- Much ado about pauline.
Includes bibliographical references and index.
Keywords: WOMEN SURFERS -- SURFING